Underestimation of dose--response relationship with particular reference to the relationship between the dietary intake of mercury and its concentration in blood - Sherlock, J C; Quinn, M J (Human & experimental toxicology, 1988)
Wide discrepancies have been observed between controlled and uncontrolled intake studies of the relationship of blood mercury concentration to intake of mercury. The probable reason for the apparent discrepancies is that the within-subject variation of mercury intake in the uncontrolled studies was almost certainly considerably larger than the within-subject variation in blood mercury concentration; in these circumstances, the apparent slope obtained from a linear regression of blood mercury on intake will invariably be much smaller than the true slope. Studies of the exposure or intake of any substance should therefore include a consideration of the likely within-subject variation in the exposure or intake relative to that in the effect.